Characterization Of Cytokines in HIV-Infected People Children With Acute Rhinosinusitis - Narzullaev N.U (Genius Publishing Group, 2022)
Currently, cytokines have been identified as a new independent system of regulation of the main functions of the body, associated, first of all, with maintaining homeostasis during the introduction of pathogens and disruption of tissue integrity. It is known that cytokines are a group of polypeptide mediators involved in the formation and regulation of the body's defense reactions
Keywords: HIV-infected; cytokines; associated; reactions